Deletion to scattered graph classes II - improved FPT algorithms for deletion to pairs of graph classes - Jacob, Ashwin; Majumdar, Diptapriyo; Raman, Venkatesh (Journal of computer and system sciences, 2023)
The problem of deletion of vertices to a hereditary graph class is a well-studied problem in parameterized complexity. Recently, a natural extension of the problem was initiated where we are given a finite set of hereditary graph classes and we determine whether k vertices can be deleted from a given graph so that the connected components of the resulting graph belong to one of the given hereditary graph classes. The problem is shown to be fixed parameter tractable (FPT) when the deletion problem to each of the given hereditary graph classes is fixed-parameter tractable, and the property of being in any of the graph classes is expressible in the counting monodic second order (CMSO) logic. This paper focuses on pairs of specific graph classes (Π1,Π2) in which we would like the connected components of the resulting graph to belong to, and design simpler and more efficient FPT algorithms.